Correlative analysis between morphology and mechanical properties of poly-3-hydroxybutyrate (PHB) blended with polycarprolactone (PCL) using solid-state NMR. (November 2020) - Nishida, Masakazu; Yasuda, Kohei; Nishida, Masahiro
Abstract: Blends of poly(3-hydroxybutyrate) (PHB) and poly(caprolactone) (PCL) were evaluated using multiscale instrumental analyses to reveal the effects of blend ratio and crosslinking reagent. In the multiscale instrumental analyses, molecular mobility from molecular to nano scales was examined by solid-state NMR, while the morphology at the micron scale was revealed by scanning electron microscopy (SEM). PHB-rich blends adopted a sea-island morphology and showed a larger maximum stress due to dispersed PHB filler. A PCL-rich blend also adopted a sea-island morphology but the sea domain consisted of PCL and showed a larger strain at break. An equal ratio PHB/PCL blend had a bicontinuous morphology which showed lower maximum stress and lower strain at break because of large hemispherical defects. The crosslinking reagent changes these heterogeneous morphologies of PHB/PCL blends to homogeneous at the micron scale, which improved tensile properties. Even though the molecular mobility changed with the polymer content and the crosslinking reagent, the bicontinuous and homogeneous morphologies more significantly affected the tensile properties of the PHB/PCL blends. Highlights: Both PHB-rich and PCL-rich PHB/PCL blends showed sea-island morphology. An equal ratio PHB/PCL blend had lower tensile properties because of bicontinuous. The crosslinker homogenized the blends, enhancing 1 H spin-lattice relaxation. The crosslinker changed slow mobility depending on flexibility of component. Morphology and mobility changes due to the crosslinker improved tensile properties.